Effects of hexavalent chromium on the biology of Steinernema feltiae: evaluating sublethal endpoints for ecotoxicity testing - Anique Godjo; Darren Mc Donald; Lucile Ansaldi; Islam A. A. Darwish; John L. Byrne; Thomais Kakouli-Duarte (PLoS ONE, 2025)
Essential information about the effects of a pollutant on an ecosystem can be obtained by observing how it influences a bioindicator organism. Hexavalent chromium (Cr VI+) naturally occurs in Irish agricultural soils at levels of up to 250 mg/kg, which raises concerns about potential negative impacts on human health and the surrounding areas. This research aimed to assess the sublethal effect concentrations (up to 300 ppm) of Cr VI + on the entomopathogenic nematode (EPN) Steinernema feltiae focusing on endpoints such as nematode movement and host finding ability in contaminated sand and pathogenicity, percentage penetration, sex ratio and reproduction in Galleria mellonella. To achieve that, an Irish isolate of S. feltiae [strain SB 12 (1)], was used in all experiments. The attraction of nematodes to the insect host was tested using PVC tubes of various lengths, containing sand with various concentrations of Cr VI + (50-300 ppm in increments of 50). The replication was tenfold and the insect mortality was recorded at the end of the experiment. Results showed that there was a significant effect of Cr VI + on the pathogenicity, movement and host finding ability of the nematodes in contaminated sand, and on the percentage of penetration in an insect host. However, no significant effects among the studied Cr VI + concentrations were observed in S. feltiae reproduction in G. mellonella. Similarly, the presence of the toxicant (at low concentration of 12ppm) did not affect the growth of the nematode symbiotic bacteria in liquid and solid media (TSA and NBTA). Reproduction, unlike the other sublethal parameters tested, appeared not to be an optimal endpoint for assessing soil Cr VI + risk contamination. Overall, this study confirms the excellent potential of S. feltiae to be used as a suitable sentinel organism in assessing the risk of Cr VI + soil contamination especially in the contexts of agriculture and soil health.